2012
DOI: 10.1111/j.1460-6984.2012.00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Sentence repetition in children with specific language impairment: an investigation of underlying mechanisms

Abstract: The data support a multifaceted view of SR with a role for syntactic knowledge, WM and STM. 'Redintegration', whereby long-term memory representations are used to maintain information in short-term memory, is likely to be a key process. Specific errors in the SLI group are likely to reflect difficulties with underlying syntactic representations. Children with SLI may be more dependent on phonological STM than typically developing children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
110
3
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(129 citation statements)
references
References 30 publications
10
110
3
6
Order By: Relevance
“…It was typical of late talkers to make several types of errors in producing one sentence. The results confirmed that sentence repetition was a useful marker for processing deficits of late talkers (Everitt et al, 2013;Riches, 2012). Also, in nominal inflection the profile of late talkers was similar to the one of typically developing children.…”
Section: Morphosyntactic Profile Of Late Talkerssupporting
confidence: 75%
See 2 more Smart Citations
“…It was typical of late talkers to make several types of errors in producing one sentence. The results confirmed that sentence repetition was a useful marker for processing deficits of late talkers (Everitt et al, 2013;Riches, 2012). Also, in nominal inflection the profile of late talkers was similar to the one of typically developing children.…”
Section: Morphosyntactic Profile Of Late Talkerssupporting
confidence: 75%
“…Lause loomeoskuse uurimisel kasutati lisaks esilekutsutud järelekordamise meetodit (ingl elicited imitation method), mis on suunatud esilekutsumisega võrreldes lapsele lihtsam (ei eelda lause semantilist kavandamist), kuid või maldab uurida nii keelelise info töötlust kui ka olemasolevaid keelelisi tead misi. Sel viisil on võimalik uurida ka spontaanses kõnes harva kasutatavate lausemallide omandatust (Polišenská, Chiat, & Roy, 2015;Riches, 2012). Mõõtevahendit ja vastuste kodeerimise süsteemi katsetati kaks korda (2014. aasta sügisel ja 2015. aasta kevadel), mille tulemusena täpsustati ja paran dati keelematerjali valikut, kodeerimissüsteemi ja pildimaterjali kvaliteeti.…”
Section: Mõõtevahendid Ja Protseduurunclassified
See 1 more Smart Citation
“…Some theories propose that a deficit in phonological short-term memory and/or a deficit in linguistic knowledge make language processing difficult (see Riches, et al, 2010 for a recent review). Another possibility is more domain general in nature: the generalized slow processing hypothesis (Kail, 1994; Miller, Leonard, Kail, Zhang, Toblin & Francis, 2006) proposes subtle differences in dealing with complex information, including language.…”
mentioning
confidence: 99%
“…It is more difficult for less able language users, including young children. While it is arguably possible to repeat short sentences exclusively by means of phonological short-term memory, longer and/or more syntactically complex sentences require the support of linguistic representations (Klem, Melby-Lervåg, Hagtvet, Lyster, Gustafsson, & Hulme, 2015;Lust, Flynn, & Foley, 1996;Riches, 2012;Slobin & Welsh, 1968). Different components of long-term knowledge are involved, with morphosyntax and lexical phonology being particularly important, but semantics and prosody also play a role Gathercole, Willis, and Adams (2004) have argued that the episodic buffer is involved during sentence repetition because information from phonological short-term memory needs to be integrated with the products of semantic and syntactic analysis.…”
Section: Introductionmentioning
confidence: 99%